Assessment of the Constraints Perceived by the Self-Help Groups Members and Impact of on their Livelihood (Indian Journal of Extension Education, 2020)
Self-Help Group (SHG) program a pragmatic approach is initiated as a self-employment program in the jargon of poverty eradication measures as well as to improve their livelihood and empowerment. This study was designed to trace out the constraints and impact of Self-Help Groups in women empowerment in Bhiwani district of Haryana, India. The research area was selected purposively and data was collected from different Self-Help Groups selected randomly from 4 blocks and 8 villages and fifteen respondents per village on the basis of their participation in SHG activities. The results revealed that the majority of the respondents (42%) perceived family responsibility as major constraint due to which they were unable to take part in Self Help Group (SHG) activities. Among Bank-SHG coordination constraints, 28.70 per cent respondents perceived that bank officials’ perception about SHGs is poor as major constraint. Maximum respondents (35.70%) faced marketing problems due to distant location of market as major institutional constraint. Among educational constraints 39.5 per cent of the respondents perceived having lack of knowledge about advantages and facilities provided by the government as major constraint. Other major problems perceived by the respondents in effective functioning were: price problems, delay in getting loans, improper demand and supply chain of commodities, and transportation. The SHGs could be used as an effective mechanism for technology dissemination to support the public extension system, social and mutual learning, institutionalized process of empowerment, conflict management, participatory extension and sustainable and equitable development.